1998
DOI: 10.1021/ja963990q
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spectroscopic Studies of CH3OH Chemisorption on Cu2O and ZnO Single-Crystal Surfaces:  Methoxide Bonding and Reactivity Related to Methanol Synthesis

Abstract: Adsorption of CH 3 OH on Cu 2 O(111), ZnO(0001), and ZnO(1010) has been investigated with XPS, NEXAFS, variable-energy photoelectron spectroscopy (PES), and SCF-XR Scattered Wave (SW) molecular orbital calculations. At high coverage (g25.0L), CH 3 OH is adsorbed as molecular multilayers on all three surfaces. At low temperatures (140 K) and coverage (0-0.6L), CH 3 OH is deprotonated to form chemisorbed methoxide on all of the surfaces investigated. Under these conditions the C1s XPS peak positions are 289.5, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 75 publications
5
50
0
Order By: Relevance
“…This result is in agreement with spectroscopic studies on the chemisorption of MeOH on ZnO single-crystal surfaces (0001 and 1010), which at low coverage also show exclusively dissociative adsorption with deprotonation, even at 140 K. [20] No experimental binding energy was reported. In contrast to MeOH, the addition of methanethiol to the ZnO cluster gave two products: molecular adduct 10 and mixed hydroxo mercapto complex 10 a resulting from dissociative adsorption [Eqs.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This result is in agreement with spectroscopic studies on the chemisorption of MeOH on ZnO single-crystal surfaces (0001 and 1010), which at low coverage also show exclusively dissociative adsorption with deprotonation, even at 140 K. [20] No experimental binding energy was reported. In contrast to MeOH, the addition of methanethiol to the ZnO cluster gave two products: molecular adduct 10 and mixed hydroxo mercapto complex 10 a resulting from dissociative adsorption [Eqs.…”
supporting
confidence: 90%
“…Expectedly, the tetrahapto form is more stable but only slightly so [Eqs. (20) and (21)], since the bonding geometry at the two five-coordinate zinc atoms of 16 a is far from optimum ( Figure 5). …”
mentioning
confidence: 99%
“…Differences in reactivity of the ZnO surfaces for the adsorption and decomposition of methanol [86][87][88][89][90] as well as formic acid [86,[91][92][93][94] on the polar and the non-polar surfaces have already been known for a long time. It was proposed that the interaction of methanol with any of the common ZnO surfaces readily led to the formation of methoxy (methoxide) species (CH 3 O) due to a heterolytic splitting of the O-H bond [87,90].…”
Section: The Interaction With Methanolmentioning
confidence: 99%
“…It was proposed that the interaction of methanol with any of the common ZnO surfaces readily led to the formation of methoxy (methoxide) species (CH 3 O) due to a heterolytic splitting of the O-H bond [87,90]. Only at low temperatures and high coverages the formation of molecular multilayers was observed using different electron spectroscopic techniques [90].…”
Section: The Interaction With Methanolmentioning
confidence: 99%
“…Using metalorganic chemical vapor deposition (MOCVD), Jeong et al reported the formation of 2D p-Cu 2 O/n-ZnO films with rectifying behavior recently [7]. It is known that Cu 2 O is a natural ptype direct-gap semiconductor with a cubic crystal structure and a room temperature bandgap energy of 2.1 eV [8]. It has also been predicated that Cu 2 O is promising for photovoltaic applications with theoretical energy conversion efficiency of 20% [9].…”
Section: Introductionmentioning
confidence: 99%